Numerical modeling of steel fiber reinforced concrete with a discrete and explicit representation of steel fibers - A. G. Bitencourt, Luís; Manzoli, Osvaldo L. [UNESP]; Bittencourt, Túlio N.; Vecchio, Frank J. (Elsevier, 2019)
This work presents a novel numerical model based on the use of coupling finite elements to simulate the behavior of steel fiber reinforced concrete (SFRC) with a discrete and explicit representation of steel fibers. The material is described as a composite made up by three phases: concrete, discrete discontinuous fibers and fiber-matrix interface. The steel fibers are modeled using two-node finite elements (truss elements) with a one-dimensional elastoplastic constitutive model. They are positioned using an isotropic uniform random distribution, considering the wall effect of the mold. A non-rigid coupling procedure is proposed for modeling the complex nonlinear behavior of the fiber-matrix interface by adopting an appropriate constitutive damage model to describe the relation between the shear stress (adherence stress) and the relative sliding between the matrix and each fiber individually. An isotropic damage model including two independent scalar damage variables for describing the concrete behavior under tension and compression is considered. To increase the computability and robustness of the continuum damage models used to simulate matrix and interface behavior, an implicit-explicit integration scheme is used. Numerical examples involving a single fiber and a cloud of fibers are performed. Comparisons with experimental results demonstrate that the application of the numerical strategy for modeling the behavior of SFRC is highly promising and may constitute an important tool for better understanding the effects of the different aspects involved in the failure process of this material.
Keywords: Concrete; Coupling finite element; Crack propagation; Damage constitutive model; Impl-Ex integration scheme; Steel fiber